The Recognition of Excessive blood loss At ChildbirTh (REACT) Study: a two‐phase exploratory, sequential mixed methods inquiry using focus groups, interviews and a pilot, randomised crossover study. (27th May 2021) - Hancock, A; Weeks, AD; Furber, C; Campbell, M; Lavender, T
Abstract : Objectives: To explore how childbirth‐related blood loss is evaluated and excessive bleeding recognised; and to develop and test a theory of postpartum haemorrhage (PPH) diagnosis. Design: Two‐phase, exploratory, sequential mixed methods design using focus groups, interviews and a pilot, randomised crossover study. Setting: Two hospitals in North West England. Sample: Women (following vaginal birth with and without PPH), birth partners, midwives and obstetricians. Methods: Phase 1 (qualitative): 8 focus groups and 20 one‐to‐one, semi‐structured interviews were conducted with 15 women, 5 birth partners, 11 obstetricians, 1 obstetric anaesthetist and 19 midwives ( n = 51). Phase 2 (quantitative): 11 obstetricians and ten midwives ( n = 21) completed two simulations of fast and slow blood loss using a high‐fidelity childbirth simulator. Results: Responses to blood loss were described as automatic, intuitive reactions to the speed, nature and visibility of blood flow. Health professionals reported that quantifying volume was most useful after a PPH diagnosis, to validate intuitive decisions and guide ongoing management. During simulations, PPH treatment was initiated at volumes at or below 200 ml (fast mean blood loss 79.6 ml, SD 41.1; slow mean blood loss 62.6 ml, SD 27.7). All participants treated fast, visible blood loss, but only half treated slow blood loss, despite there being no difference in volumes (difference 18.2 ml, 95% CI −5.6 to 42.2 ml, P = 0.124). Conclusions: Experience and intuition, rather than blood loss volume, inform recognition of excessive blood loss after birth. Women and birth partners want more information and open communication about blood loss. Further research exploring clinical decision‐making and how to support it is required. Tweetable abstract: During a PPH, clinical decision‐making is intuitive with clinicians treating as soon as excessive loss is recognised. Tweetable abstract: During a PPH, clinical decision‐making is intuitive with clinicians treating as soon as excessive loss is recognised.